Frameshift-derived neoantigens constitute immunotherapeutic targets for patients with microsatellite-instable haematological malignancies: Frameshift peptides for treating MSI+ blood cancers - Maletzki, Claudia; Schmidt, Fabian; Dirks, Wilhelm G.; Schmitt, Michael; Linnebacher, Michael (European journal of cancer, 2013)
Purpose - Microsatellite instability (MSI) resulting from loss of functional DNA mismatch repair was recently found in various haematological disorders. In coding sequences, MSI leads to frameshift mutations (FSMs) and the production of C-terminally altered proteins which are foreign to the immune system. Here, we wondered whether these frame-shifted peptide (FSP) sequences represent tumour-specific antigens also for MSI+ leukaemia and lymphomas (L/L). - Material and methods - A total of 33 coding region microsatellites were examined in MSI+ L/L cell lines for the presence of FSMs. Thereafter, recognition of MSI+ cells by established FSP-specific CD8+ T cell lines was quantified using interferon (IFN)-γ enzyme-linked immunospot (ELISpot) assays. In each experiment, MSI+ L/L cell lines and T2 targets exogenously loaded with the cognate peptide (=internal control) were employed. Supplementary, lytic activity towards tumour cells was analysed by standard chromium release assay (51Cr). - Results - Mutational profiling of 33 coding microsatellite loci in nine MSI+ L/L cell lines revealed instability in at least nine microsatellites. In each cell line, a distinct mutational profile was observed. Only three of the 33 loci were stable. FSP-specific and human leukocyte antigen-A2 (HLA-A2)-restricted T cells specifically recognised MSI+ L/L cells endogenously expressing TGFβRII(-1), Caspase 5 (-1) and MSH3 (-1) in ELISpot assays. Moreover, specific killing of Caspase 5 (-1) and MSH3 (-1) expressing L/L cell lines was achieved in functional cytotoxicity assays. - Conclusion - Data presented here expand the importance of FSPs as shared and general tumour-specific antigens. Consequently, they open new avenues for specific immunotherapies not only for solid but also for MSI+ haematological malignancies.
Gesehen am 17.06.2021